The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12890-022-02112-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophils to lymphocytes and platelets ratio for 28-day mortality in patients with acute respiratory distress syndrome: a retrospective study

Abstract: Background Acute respiratory distress syndrome (ARDS) is a rapidly progressive and fatal respiratory failure disease that often occurs in critically ill patients. Since ARDS is associated with immune dysregulation and coagulation abnormalities, it is necessary to identify an appropriate predictor that can accurately predict ARDS mortality based on its pathophysiology. Therefore, this study aimed to evaluate the clinical value of neutrophils to lymphocytes and platelets ratio (N/LPR) in predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…NLR is an indicator re ecting the in ammatory state in vivo, which is easy to obtain clinically. A large number of studies have shown that NLR is an signi cant prognostic marker for critical diseases such as heart failure, myocardial infarction, ARDS and so on [16][17][18][19]. Moreover, several studies have also found that the increase of NLR before and after catheter ablation was related to the increase of postoperative atrial brillation recurrence [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…NLR is an indicator re ecting the in ammatory state in vivo, which is easy to obtain clinically. A large number of studies have shown that NLR is an signi cant prognostic marker for critical diseases such as heart failure, myocardial infarction, ARDS and so on [16][17][18][19]. Moreover, several studies have also found that the increase of NLR before and after catheter ablation was related to the increase of postoperative atrial brillation recurrence [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In acute respiratory distress syndrome (ARDS), which progresses with severe respiratory failure in adults, NLR, MLR, and PLR both increase with the severity of the disease and reach higher values in patients who died. [24][25][26][27][28] In the neonatal area, high NLR, MLR and PLR levels have been found to be useful diagnostic tools for hypoxic ischemic encephalopathy, PDA, EOS, ROP, IVH, and NEC. [10][11][12][13][14][15] However, the role of systemic inflammatory indeces in the diagnosis of RDS in premature infants is not clearly known.…”
Section: Discussionmentioning
confidence: 99%
“…26 In ARDS, platelets interact with neutrophils, causing more neutrophil recruitment, endothelial and immune cell activation, and formation of platelet–neutrophil complexes. 25 The increase in SII as a result of platelet activation, apoptosis in lymphocytes, and increase in neutrophils may reflect the inflammation status more comprehensively by reflecting the balance between platelet, lymphocyte count, and neutrophil count. 26 Thus, it can be used as a prognostic biomarker in patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation may induce secondary brain injury by aggravating blood-brain barrier(BBB) injury, microvascular failure, brain edema, oxidative stress and directly induce neuronal cell death (7). Neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) are frequently adopted indicators of systemic inflammation and infection (8). It is worth noting that some studies suggest that NLR and PLR probably have better predictive abilities than traditional inflammatory factors (9).…”
Section: Introductionmentioning
confidence: 99%